Increased oxidative stress and oxidative DNA damage in non-remission schizophrenia patients. Issue 1 (30th September 2015) - Sertan Copoglu, U.; Virit, Osman; Hanifi Kokacya, M.; Orkmez, Mustafa; Bulbul, Feridun; Binnur Erbagci, A.; Semiz, Murat; Alpak, Gokay; Unal, Ahmet; Ari, Mustafa; Savas, Haluk A.
Abstract: Increasing evidence shows that oxidative stress plays a role in the pathophysiology of schizophrenia. But there is not any study which examines the effects of oxidative stress on DNA in schizophrenia patients. Therefore we aimed to assess the oxidative stress levels and oxidative DNA damage in schizophrenia patients with and without symptomatic remission. A total of 64 schizophrenia patients (38 with symptomatic remission and 26 without symptomatic remission) and 80 healthy volunteers were included in the study. 8-hydroxydeoxyguanosine (8-OHdG), total oxidant status (TOS) and total antioxidant status (TAS) were measured in plasma. TOS, oxidative stress index (OSI) and 8-OHdG levels were significantly higher in non-remission schizophrenic (Non-R-Sch) patients than in the controls. TOS and OSI levels were significantly higher in remission schizophrenic (R-Sch) patients than in the controls. TAS level were significantly lower and TOS and OSI levels were significantly higher in R-Sch patients than in Non-R-Sch patients. Despite the ongoing oxidative stress in patients with both R-Sch and Non-R-Sch, oxidative DNA damage was higher in only Non-R-Sch patients compared to controls. It is suggested that oxidative stress can cause the disease via DNA damage, and oxidative stress plays a role in schizophrenia through oxidative DNA damage. Highlights: TOS, OSI, 8-OHdG levels were higher in non-remission schizophrenia patients. TOS and OSI levels were higher in remission schizophrenia (R-Sch) patients. TAS was lower, TOS and OSI were higher in R-Sch patients compared to Non-R-Sch. Oxidative stress increased in schizophrenia patients independently from remission. Oxidative DNA damage is increased in only Non-R-Sch patients compared to controls.